Sustainable Development in East Java Indonesia: A Bibliometric Review Based on Scopus Database Using Critical Paradigm - Ahmad Hudaifah; Shochrul Rohmatul Ajija (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2026)
East Java, as the second-largest economy and hub of Eastern Indonesia, strives to improve its sustainable development indicators. Scholars affiliated with universities contribute to these efforts. The study aims to examine scholarly contributions indexed in the Scopus database through a critical paradigm using a bibliometric systematic review from 1994 to 2026. The study discovered that conference proceedings across various university affiliations publish the majority of articles with sustainable development keywords. The study has also found that the 231 themes are being synthesised into a 63 per cent focus on meso-macro foundational perspectives of business entities and country regulatory stakeholders and a lesser focus on micro-foundational perspectives on individual people-centred development. In addition, regarding the balance of economic, social, and environmental pillars, the study found that environmental and governance topics dominate the researcher’s interest in sustainable development in the East Java context. Unfortunately, most authors in the East Java context overlook the philosophical underpinning, political context, and social justice equity as significant topics. Thus, by suggesting critical perspectives on sustainable development, a focus on individual behaviour, and multidisciplinary aspects of research, the authors can help the East Java government expedite sustainable development through research-based policies.